2008
DOI: 10.1007/s10763-007-9120-9
|View full text |Cite
|
Sign up to set email alerts
|

Misconceptions of Turkish Pre-Service Teachers about Force and Motion

Abstract: The purpose of this study was to diagnose the misconceptions held by preservice physics teachers about force and motion. The secondary aim of the study was to detect whether misconceptions vary according to gender, educational level, and culture. The study was conducted with 79 student-teachers attending to one of the largest faculties of education in Turkey. Force Concept Inventory (FCI) was used to diagnose studentteachers' misconceptions. FCI is a conceptual test consisting of 29 multiple choice items. Each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
3
18

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 47 publications
11
68
3
18
Order By: Relevance
“…The first thing one notices from the table is the weak overall performance of all students even after instructions. Weak performance on the FCI by our students is of no surprise to us as similar results have been reported before in many studies around the world [15][16][17][18]. It's not in the scope of this study to try to explain this weakness or suggest solutions for it but its part of our future planned projects and therefore there will be no farther discussion on this here.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The first thing one notices from the table is the weak overall performance of all students even after instructions. Weak performance on the FCI by our students is of no surprise to us as similar results have been reported before in many studies around the world [15][16][17][18]. It's not in the scope of this study to try to explain this weakness or suggest solutions for it but its part of our future planned projects and therefore there will be no farther discussion on this here.…”
Section: Resultssupporting
confidence: 83%
“…These low gains also suggest that there is little difference made by our instructions in students' performance which is similar to results reported by Hake (1998) and Viiri (1996) [18,19]. This result by itself deserves more attention and efforts are ongoing to start the next stage in this research project.…”
Section: Resultssupporting
confidence: 81%
“…Even though male and female students scored differently on the FCI tests [1], results of this study showed clear evidence that they all hold same misconceptions. Similar results were reported before regarding the universal nature of Newtonian mechanics misconceptions [10][11][12][13]. This report serves as one of the first few steps in our main project; we aim at a whole evaluation and then reconstruction of our physics education process at our school.…”
Section: Discussionsupporting
confidence: 72%
“…The UCMMT was administered to physics education students in their first, second and third year of the students in 2009-2010academic year. Later, in 2011-2012 academic year the same instrument was used again to the same students who were in their third, fourth and fifth years of their program.…”
Section: Nef-efmedmentioning
confidence: 99%